Laminitis in dairy cows - PANOUSIS (Ν. ΠΑΝΟΥΣΗΣ) N.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ) H. (Journal of the Hellenic Veterinary Medical Society, 2018)
Laminitis is currently considered one of the commonest causes of lameness in dairy cows in Greece. Nutrition, especially rations based on concentrated feedstuffs, herd management and genetic factors are involved in the etiopathogenesis of the disease. The causative agents, formed usually in the digestive tract, reach the heels via systemic circulation, damaging initially the dermis and subsequently the deeper tissues, thus disrupting normal keratin formation. The disease is characterized by a chronic, or even subclinical course and pathognomonic lesions, like ecchymoses and ulcers in the hindlimb hoof soles. Since early diagnosis is usually missed, preventive measures focused mainly on proper nutrition, herd management and breeding strategies constitute the only possible treatment.